PENERAPAN GRAFIK KENDALI JUMLAH KUMULATIF UNTUK MENDETEKSI PERGERAKAN KURS MATA UANG (Studi Kasus: Kurs Jual dan Kurs Beli Dollar Amerika) - Silvia Julietty Sinaga; Mustafid Mustafid; Sugito Sugito (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2017)
The Average Control Chart ( can be used to see if there has been an average change in a process. But this graph has a weakness that is not sensitive to small average shifts. The Cumulative Sum Control Chart (CUSUM) is considered to be more effective in detecting small average process shifts, because it combines information taken from multiple samples by describing the cumulative number of sample deviations from the target value. Both of these graphs are used to detect currency exchange rate shifts with the conclusion that the exchange rate of US Dollar (USD) to Rupiah (IDR) are out of control. The Average Run Length (ARL) value of the CUSUM Chart tends to be smaller than ARL of the chart. The ARL of CUSUM Control Chart for the selling rate and buying rate is 14,4269 and 19,3798. The ARL of chart with the 3 sigma limit is 370,37. CUSUM control chart also gives the result that the average of selling rate has increased from 13,022 to 13,200 and the average of buying rate has decreased from 13,022 to 12,6027. This means that the Dollar selling price in the bank will increase/expensive while the Dollar purchase price will decrease/cheaper. Keywords: Exchange Rate, Average Control Chart, Cumulative Sum Control Chart (CUSUM), Average Run Length (ARL), US Dollar (USD), Rupiah (IDR)